Royal bastards - Shvarts, Andrew (2017)
Tilla, the illegitimate daughter of Lord Kent, bands together with other outcasts in an attempt to prevent civil war and protect Lyriana, a sheltered, visiting princess whose life is in danger.
Tilla, the sixteen-year-old illegitimate daughter of Lord Kent, spends her days exploring the tunnels beneath the castle and her nights drinking with the servants, passing out in her half-brother's room. When they witness a crime that is part of a brutal coup, Tilla and her fellow bastards band together with other outcasts in an attempt to prevent civil war and protect Lyriana, a sheltered, visiting princess whose life is in danger.
Maps on lining papers.
Keywords: Fathers and daughters -- Fiction; Illegitimacy -- Fiction; Insurgency -- Fiction; Princesses -- Fiction; Magic -- Fiction; Fantasy; Fathers and daughters; Illegitimacy; Insurgency; Magic; Princesses; Adventure fiction; Young adult fiction; Adventure stories; Young adult fiction; Science fiction; Fantasy fiction; Fantasy fiction; Fiction